Colitis-associated neoplasia: molecular basis and clinical translation - Försch, Sebastian; Neurath, Markus (Cellular and Molecular Life Sciences, 2014)
Crohn's disease and ulcerative colitis are both associated with an increased risk of inflammation-associated colorectal carcinoma. Colitis-associated cancer (CAC) is one of the most important causes for morbidity and mortality in patients with inflammatory bowel diseases (IBD). Colitis-associated neoplasia distinctly differs from sporadic colorectal cancer in its biology and the underlying mechanisms. This review discusses the molecular mechanisms of CAC and summarizes the most important genetic alterations and signaling pathways involved in inflammatory carcinogenesis. Then, clinical translation is evaluated by discussing new endoscopic techniques and their contribution to surveillance and early detection of CAC. Last, we briefly address different types of concepts for prevention (i.e., anti-inflammatory therapeutics) and treatment (i.e., surgical intervention) of CAC and give an outlook on this important aspect of IBD.
EVALuna2:1861